THE RELATIONSHIP BETWEEN CHARACTERISTICS OF CREATIVE THINKING IN MATHEMATICS AND WRITING TO LEARN MATHEMATICS AMONG IX STANDARD STUDENTS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mathematics is in all walks of life from the worlds of business and technology, to thesciences, to medicine, and even to environmental and management. Very few researchstudies have been conducted in mathematical creativity and writing to learn mathematicsstudents who are conventional in thought and readily conform to the school norms areconsidered better for academic tasks and they are creative students who were seen as threatsand became challenging for teachers. In this study the investigator has attempted to study theinfluences of various demographic variables like gender, localityand medium of instruction.The researcher adopted normative survey method. 500 students of IX standard from 8schools in Salem District were selected as sample by stratified random sampling technique.Characteristics of creative thinking in mathematics scale constructed by Renzulhi, J.S et.al(2004). This contained 40 items. Its reliability value was 0.80. Writing to learn mathematicsscale constructed by Edel Mary Reilly (2007). This contained 20 items on 3 dimensions. Areliability co - efficient of 0.84 was obtained using split half method. Quantitative dataanalysis was done. Results shows that IX Standard Boys and Girls do not differ inmathematical characteristics, creative characteristics and characteristics of the potentiallycreative thinking in mathematics and IX Standard rural and urban students do not differ intheir Mathematics in general, writing in math class, Math teacher.